The heterogeneity of default costs: Evidence from recent sovereign debt crises - Markus Jorra (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
This paper examines the costs of recent sovereign defaults using synthetic control methods, a novel econometric technique based on comparative case studies. Evidence on the effects of debt crises is thus presented on a case-by-case basis, uncovering large variations in country-specific experiences. Our estimates of cumulated output losses, e.g., range between 8.5% and 23% depending on the considered default episode. Further differences concern the persistence and likely causes of these costs. In particular, our results are consistent with the selective use of direct trade sanctions as punishment for sovereign defaults.
Keywords: F34; H63; C21; C23; 330; sovereign defaults; default costs; case study; synthetic control methods; Staatsbankrott; Wirkungsanalyse; Kosten; Test; Vergleich; Theorie; Pakistan; Ecuador; Argentinien; Uruguay; Dominikanische Republik